EDUKASI UNTUK MENINGKATKAN PENGETAHUAN HIPERTENSI PADA MASYARAKAT DESA WIROGUNAN KECAMATAN KARTASURA KABUPATEN SUKOHARJO - Muhammad Mukhlis Cahyadi; Dwi Astuti; Anida Azkia Fitri; Farita Adhynda Amithya; Yuliana Lestari; Salwa Malihatunnisa; Sherly Nur Janah; Kharina Indira Astuti; Fara Nabila; Krisna Wibowo; Sevtya Nur Hasanah; Lilis Apriliyani; Farida Nur Isnaeni (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2024)
The results of an initial survey of the people of Wirogunan Village showed that hypertension became one of the health problems with the highest prevalence of 51.18%, with risk factors found in the form of unhealthy diet and lifestyle. Therefore, counseling is carried out related to knowledge about hypertension and diet recommended by sufferers. The method used is lectures equipped with pre-tests and post-tests. The information media used in this activity is a PowerPoint presentation about hypertension. The result of this counseling was an increase in knowledge among villagers with good categories from before receiving counseling by 60.5% and after receiving counseling by 84.2%. Increased knowledge consists of understanding the causes, prevention of hypertension, and diet for people with hypertension. Based on the results of Wilcoxon's non-parametric statistical test, a value of p = 0.003 (p<0.05) was obtained. Then Ho was rejected, meaning there is a difference in the level of knowledge of Wirogunan Village residents before and after receiving hypertension counseling.